THE MINERALOGICAL CHARACTERISTICS OF VOLCANIC SOILS FROM NORTH-LAMPUNG, SUMATRA INDONESIA - ALKASUMA, .; BADAYOS, R.B (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2003)
The study took place in the volcanic soils of Mt. Hulu Sabuk in North Lampung Regency, Lampung Province. The research had been conducted from June to October 2000. The objective of study was to reveal the mineralogical characteristics of volcanic soils, especially in the study area. The methodologyused was transect/landscape analysis by studying of six soil profiles that supported by mineralogical analyses of optical, X-ray diffraction and differential thermal of soil samples. The results of the study showed that opaque minerals and quartz dominate the soil mineralogy of the study area. While the weatherable minerals like volcanic glass, feldspars, amphiboles, and pyroxenes were encountered in small amounts. The secondary minerals of clay fraction were occupied by kaolinite and gibbsite. The characteristics of soil minerals indicated that the volcanic soils in the study area are highly weathered and already developed.